Dual inhibition of the Echinococcus multilocularis energy metabolism - Chaudhry, Sheena; Zurbriggen, Raphael; Preza, Matías; Kämpfer, Tobias; Kaethner, Marc; Memedovski, Roman; Scorrano, Nathalie; Hemphill, Andrew; Doggett, Joseph Stone; Lundström-Stadelmann, Britta (Frontiers in Veterinary Science, 2022)
Alveolar echinococcosis is caused by the metacestode stage of the zoonotic parasite Echinococcus multilocularis. Current chemotherapeutic treatment options rely on benzimidazoles, which have limited curative capabilities and can cause severe side effects. Thus, novel treatment options are urgently needed. In search for novel targetable pathways we focused on the mitochondrial energy metabolism of E. multilocularis. The parasite relies hereby on two pathways: The classical oxidative phosphorylation including the electron transfer chain (ETC), and the anaerobic malate dismutation (MD). We screened thirteen endochin-like quinolones (ELQs) in vitro for their activities against two isolates of E. multilocularis metacestodes and isolated germinal layer cells by the phosphoglucose isomerase (PGI) assay and the CellTiter Glo assay. For the five most active ELQs (ELQ-121, ELQ-136, ELQ-271, ELQ-400 and ELQ-437), EC50 values against metacestodes were assessed by PGI assay, and IC50 values against mammalian cells were measured by Alamar Blue assay. Further, the gene sequence of the proposed target, the mitochondrial cytochrome b, was analysed. This allowed for a limited structure activity relationship study of ELQs against E. multilocularis, including analyses of the inhibition of the two functional sites of the cytochrome b. By applying the Seahorse XFp Extracellular Flux Analyzer, oxygen consumption assays showed that ELQ-400 inhibits the E. multilocularis cytochrome bc1 complex under normoxic conditions. When tested under anaerobic conditions, ELQ-400 was hardly active against E. multilocularis metacestodes. These results were confirmed by transmission electron microscopy. ELQ-400 treatment increased levels of parasite-released succinate, the final electron acceptor of the MD. This suggests that the parasite switched to MD for energy generation. Therefore, MD was inhibited with quinazoline, which did not induce damage to metacestodes under anaerobic conditions. However, it reduced the production of succinate compared to control treated parasites (i.e. inhibited the MD). The combination treatment with quinazoline strongly improved the activity of the bc1 inhibitor ELQ-400 against E. multilocularis metacestodes under anaerobic conditions. We conclude that simultaneous targeting of the ETC and the MD of E. multilocularis is a possible novel treatment approach for alveolar echinococcosis, and possibly also other foodborne diseases inflicted by platyhelminths, which cause substantial economic losses in livestock industry.